PENGARUH INFLASI, SUKU BUNGA, UKURAN REKSA DANA, DAN UMUR REKSA DANA TERHADAP KINERJA REKSA DANA - Hermawan, Denny; Wiagustini, Ni Luh Putu (E-Jurnal Manajemen, 2016)
This study aims to determine the significance of the effect of inflation, interest rates, equity fund size, and age of mutual fund shares in fund performance shares listed on the Indonesian stock exchange. This research was conducted at the company's equity funds. The sampling method used in this research is the method nonprobability sampling with purposive sampling technique, with the criteria of equity funds that the effective date of more than five years of trading. Based on these criteria obtained a sample of 20 companies. The data in this study using non-participant observation that retrieve data on the Stock Exchange Indonesia.Model analysis used is multiple linear regression with the finding that inflation negatively affect the performance of mutual fund shares, interest rates negatively affect the performance of mutual fund shares, the size of mutual funds positive effect on the stock performance of mutual fund shares, and age equity fund positively affects the performance of mutual fund shares.
Keywords: Performance Equity Fund, Inflation, Interest Rates, Equity Fund Size, Age Equity Fund